Pemaksaan Perkawinan Berkedok Tradisi Budaya: Bagaimana Implementasi CEDAW terhadap Hukum Nasional dalam Melindungi Hak-Hak Perempuan dalam Perkawinan? - Fanny Nainggolan, Junita; Ramlan, Ramlan; Harahap, Rahayu Repindowaty (Faculty of Law, Universitas Jambi, 2022)
This article discusses the implementation of CEDAW Â into national law to protect womenâ€™s rights in marriage. Even though the convention has been ratified for decades, in social life, women are still often discriminated against. One form of discrimination in Indonesia is still a patriarchal culture that develops in society. The patriarchy that dominates the culture of society creates sexism and gender inequality that affects many aspects of human activity, one of which is the issue of marriage. In Indonesia, there are still many marriages that occur Indonesia because of forced marriages. Moreover, it is carried out under the guise of a tradition that has experienced a shift in cultural values. The choice to marry and with whom is closely related to self-determination which has been recognized in the CEDAW Convention. The results of this study indicate that in the CEDAW Convention, everyone has the same right to marry, regardless of the gender and gender of the person. However, in its implementation into national law, its implementation is still discriminatory and not yet integrated.